Asylsökandes möjligheter till meningsfulla aktiviteter : En kvalitativ studie - Boström, Malin; Firouzfar, Elina (2015)
The aim of this study was to describe the possibilities of meaningful occupations performed by an asylum seeker in northen Sweden. To examine this, ten interviews were performed with persons who have previously been asylum seekers. Four women and six men, aged 21 to 47 participated and they originally came from; Afghanistan, Eritrea, Somalia, and Syria. Data was analyzed using content analysis, resulting in the following three categories; i) The significance of the place to enable occupation, possibilities for occupations were influenced by living with other asylum seekers, where the personal sphere was nonexistent. ii) How occupations are limited by living between two worlds, participants experienced a great loss of occupation (occupational deprivation) and wished to be more active. iii) A desire to bee part of occupaitons in society, the results showed the participants' motivation and willingness to integrate into the Swedish society, despite the limited possibilities in the surrounding context. The results contribute to an understanding of the experience of the possibilities for meaningful occupations as an asylum seeker in northern Sweden. This knowledge can be of benefit to both occupational therapists, and other professions in order to promote the rights-, and the possibilities of meaningful occupations for asylum seekers. Validerat; 20150608 (global_studentproject_submitter)